RESEARCH OF DESIGN PARAMETERS OF CAVITATION NOZZLES AND OPERATING MODES OF WATER PREPARATION EQUIPMENT FOR HEATING NETWORKS IN SOLIDWORKS AND PRACTICAL USE - DUSHENKO, OLEKSANDR; TKACHUK, VITALIY; MARCHENKO, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Recently, with the increase in the number of studies on the cavitation effect on liquid media, it has been shown that cavitation jets can be practically applicable in many useful technologies. In addition to the already widely used phenomenon of acceleration of chemical reactions in the preparation of emulsions and suspensions, changing the properties and composition of water, new modern technical solutions for the use of cavitation appear. The paper considers the issue of engineering analysis of technical systems by means of computer modeling, in particular, the study of the design parameters of cavitation nozzles using the SOLIDWORKS Flow Simulation engineering analysis system, which allows conducting numerical experiments to determine their characteristics, namely, to determine the cavitation effect on changing the properties and composition of water. The paper presents the capabilities of the SOLIDWORKS Flow Simulation software product to solve the scientific and technical problem of determining the cavitation characteristics of the nozzles under study. The design parameters of cavitation nozzles were studied in SOLIDWORKS Flow Simulation for flow characteristics according to the cavitation number and the maximum mixing capacity of the liquid flow was analyzed to create intensive conditions for oxidative and hydrogen reactions in real operating modes of water treatment equipment for heating networks and practical confirmation of the operability of the proposed solutions was obtained. From the obtained results of modeling the liquid flow through the nozzles, it was established that the greatest cavitation effect is exerted according to the cavitation number at an inlet pressure of 0.12 MPa. The best effect of liquid mixing at the outlet of the nozzle was obtained in the stepped nozzle at the inlet and outlet. From the point of view of manufacturing technology, the stepped nozzle at the inlet and outlet, which was used in the experimental equipment, is more technologically advanced in terms of manufacturing. Experimental equipment was manufactured with the possibility of using individual blocks, namely a hydrostatic cavitator, a magnetization block, a vibration cavitator and their use in a complex. The practical application of the impact on the composition of tap water was evaluated by changing the indicators: pH, total mineralization (indicator - TDS), oxidation-reduction potential (ORP) and analysis of the sediment that forms over time after settling (three days). The conducted studies make it possible to design equipment for water treatment for heating networks according to the required productivity of real needs.